ANALISIS RASIO KEUANGAN PASCA AKUISISI PADA PT GARUDAFOOD PUTRA PUTRI JAYA TBK PERIODE 2020-2024 - Natalia Wulandari; Marnas; Prayetno Agustinus Sitanggang (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the development of financial ratios of PT Garudafood Putra Putri Jaya Tbk after the acquisition during the 2020-2024 period. The ratios examined include the Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Return on Assets (ROA), using a descriptive quantitative approach. Data were obtained from the company's financial statements and analyzed to observe the trend of each ratio over five years. The results indicate that the Current Ratio fluctuated and tended to decline in the final year. The Debt to Equity Ratio decreased in several periods, yet the company remained dependent on debt. The Total Asset Turnover improved toward the end of the period, although asset utilization had not reached an optimal level. The Return on Assets showed a gradual increase, indicating better asset efficiency These findings suggest that the company needs to strengthen current asset management, enhance asset utilization efficiency, and maintain a balanced capital structure between equity and debt to maximize the positive impact of the acquisition. This study provides an academic contribution as empirical evidence that the acquisition influences changes in the company’s financial ratios during the post-acquisition period.